Study on the Influence of Different Prophase Stress Levels on the Fatigue Damage Characteristics of Granite - Tianzuo Wang; Mengya Xue; Peng Sha; Fei Xue; Linxiang Wang (Shock and Vibration)
In order to reveal the influence of prophase stress levels on the fatigue damage characteristics of granite, uniaxial fatigue tests of granite with different prophase stress levels were carried out on the basis of the MTS 815.04 rock mechanics test system. The results show that, under the same number of cycles, the failure degree increases with the increase of the prophase stress level. Under the low upper limit of cyclic stress, the tangent modulus and dissipated energy increase significantly with the increase of prophase stress level at the early stage of the cycle loading, while the increasing trend is not obvious with the increase of prophase stress level at the late stage. Under the high upper limit of cyclic stress, the tangent modulus and dissipated energy are less affected by the prophase stress level. The development trend of elastic release energy is not obvious with the increase of prophase stress level, which is less affected by the number of cycles. From the damage parameters defined by dissipative energy, under the low upper limit of cyclic stress, the initial damage is less affected by the prophase stress level. With the increase of the number of cycles, the influence of the prophase stress level on the development trend of the damage variable increases gradually. And the development trend of damage variables shows “C-shaped” damage.